Iatrogenic Pectus Deformities after Sternotomy in Patients with Down Syndrome - Haje, Davi de Podestá; Aires, Jorge Henrique Carlos; Sousa, Talita Virginia Pinto de; Aquino, Fernando Aurélio de Sá (Revista Brasileira de Ortopedia, 2025)
To evaluate the incidence of pectus deformity after sternotomy in patients with Down syndrome, in addition to the clinical and radiographic characteristics.There were 20 patients with sternotomy history during childhood and a control group (n = 20). The chest was clinically evaluated for the presence and type of pectus deformity, severity, and the clinical sternal body length. Radiographic examinations were used to evaluate any abnormalities.From the total, 85% (n = 17) presented with pectus deformities (41% lateral pectus carinatum, 65% mild severity, and 29% little flexibility). In the control group, deformity occurred in 5% (n = 1). In the sternotomy group, 40% (n = 8) had a clinically shortened sternum, which did not occur in the control group (p = 0.01). Radiographic examination of the sternotomy with pectus group showed posterior angulations in the manubrium (10%), sternal shortening (38%), and irregularities in the sternal body (70%); furthermore, 36% of the children had all sternal growth plates closed, and 10% had early sterno-manubrial fusion, which did not occur in the control group.Patients presented a high incidence of pectus deformity after sternotomy (mostly mild and of the lateral carinatum type), with radiographic changes suggestive of abnormal sternal growth.
Keywords: deformity; Down syndrome; iatrogenic disease; pectus carinatum; pectus excavatum; sternotomy